Efforts to Improve the Mathematical Ability of Grade VII Students Spatial Building Materials with the Project Based Learning (PjBL) - Maulidah, Noor Mayaminiy; Mardiana, Ari; Priyo Prawoto, Budi (MATHEdunesa, 2024)
This type of research uses Classroom Action Research (CAR). The subjects in this study were class VII-C students at SMP Negeri 6 Surabaya with a total of 34 students. Research data were obtained from project sheets, evaluation questions, and activity sheets on spatial learning through the Project Based Learning (PjBL). The results of the study show that the application of the Project Based Learning (PjBL) can increase the mathematical value of geometric material in class VII-C students of SMP Negeri 6 Surabaya for the 2022/2023 academic year. The average score of students in cycle I was 59.7 and the average score of students in cycle II increased to 83 with the KKM at SMP Negeri 6 Surabaya being ? 80. And the Project Based Learning (PjBL) can meet the KKM achievement target, activity and projects in mathematics subject matter geometry. Achievement of the percentage of completeness to improve students' mathematical abilities in cycle II was 82.34% with students who completed reaching 28 students, 6 students who did not complete with further guidance through giving assignments.